QUALITY SERVICE, TRUST, SATISFACTION, IMAGE COMPANY AND CUSTOMER LOYALTY: THE EFFECT OF ORAL INFORMATION ON BANK CUSTOMERS IN SURABAYA - Fitra Mardiana; Trisa Indrawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2015)
Verbal informationcanbe one of thecapital towin the competition. Wordof mouthis astatement (personal ornon-personal) delivered by someone other than the organization (service provider) to the customer. customerloyaltycan becreated if thefirstbankto beable toprovideexcellentquality of serviceandsatisfactionto its customers. The product qualityof both goods andserviceswill contributegreatly tocustomer satisfaction, market share, and return on investment (return on investment) companies through cost reduction, improved productivity and customer satisfaction. This study to determine: a) Is there a significant positive effect of service quality on customer satisfaction?, B) Is there a significant positive effect on customer loyalty customer confidence?. C) Is there a significant positive effect on customer loyalty customer satisfaction?, d) Is there a significant positive effect on customer loyalty bank's image?. e) Is there a significant positive influence on customer loyalty verbal information? This study uses the theory of the service quality , corporate image , customer satisfaction , customer trust , customer loyalty and word of mouth marketing strategy .The method used is quantitative research . The method of selecting the sample using the method of selecting a random sample ( randomly sampling ) , while the technical implementation is accidental . This research was carried out on state-owned bank in Surabaya BNI , BRI , Bank Mandiri and BTN . The number of samples in this study 113 data collection techniques and procedures with questionnaires , interviews and literature study . While this type of data used is quantitative data . Test Validity and Reliability Research Tool application using the Statistical Program for Social Science ( SPSS ) 19.0 for Windows . Instrument reliability using Cronbach alpha coefficient . Based on test validity indicators for all the questions are valid as indicated r count for each indicator to the positive variables and greater than 0.3 . Meanwhile, for Cronbach alpha reliability shows all the indicators value is more than 0.6 so that it can be said that the instrument is reliable . However, customer satisfaction has a positive significant effect on the quality of service , customer loyalty significantly positive effect on customer satisfaction , and verbal information significantly positive effect on customer loyalty